Lower back pain on computer use on Information and Computer Technics (IT Management) students from STMIK STIKOM University Bali - Krisna Priya Ponusamy; Luh Made Indah Sri Handari Adiputra; I Made Krisna Dinata; I Made Muliarta (DiscoverSys Inc., 2020)
Background: Lower back pain is a pain syndrome that occurs in the lower back region as various causes. This disorder is most commonly found among students, especially in those who sit with the wrong body posture.Aims: The purpose of this study was to determine how does using the computer for an extended period causes lower back pain for students and to identify the prevention method of lower back pain because of using that equipment.Methods: This study used cross-sectional design using primary data through questionnaire and interview. The sample population of this research is Information and Computer Technics (IT Management) students in STMIK STIKOM University Bali. Using the entire sampling method yielded 32 samples. Results: There is a significant result of using the computer for a long time and sitting postures toward lower back pain complaints on students in STMIK STIKOM University Bali.Conclusion: Based on the results of the study is still very necessary to give attention and changes on the amount of time using a computer and sitting postures for students to support the health of students.